Linking Gene Expression and Membrane Lipid Composition of Arabidopsis . Issue 3 (18th March 2014) - Szymanski, Jedrzej; Brotman, Yariv; Willmitzer, Lothar; Cuadros-Inostroza, Álvaro
Abstract : This work examines the connection between changes in gene expression and changes in membrane lipid composition in Arabidopsis exposed to different light and temperature conditions. Three transcriptional programs identified are shown to be coordinated with changes in specific membrane lipids, further supported by lipidomic analysis of selected knockout lines. Abstract: Glycerolipid metabolism of plants responds dynamically to changes in light intensity and temperature, leading to the modification of membrane lipid composition to ensure optimal biochemical and physical properties in the new environment. Although multiple posttranscriptional regulatory mechanisms have been reported to be involved in the process, the contribution of transcriptional regulation remains largely unknown. Here, we present an integrative analysis of transcriptomic and lipidomic data, revealing large-scale coordination between gene expression and changes in glycerolipid levels during the Arabidopsis thaliana response to light and temperature stimuli. Using a multivariate regression technique called O2PLS, we show that the gene expression response is strictly coordinated at the biochemical pathway level and occurs in parallel with changes of specific glycerolipid pools. Five interesting candidate genes were chosen for further analysis from a larger set of candidates identified based on their close association with various groups of glycerolipids. Lipidomic analysis of knockout mutant lines of these five genes showed a significant relationship between the coordination of transcripts and glycerolipid levels in a changing environment and the effects of single gene perturbations.